Bacteriophage-related epigenetic natural and non-natural pyrimidine nucleotides and their influence on transcription with T7 RNA polymerase - Filip Gracias; Radek Pohl; Veronika Sýkorová; Michal Hocek (Communications Chemistry)
Abstract DNA modifications on pyrimidine nucleobases play diverse roles in biology such as protection of bacteriophage DNA from enzymatic cleavage, however, their role in the regulation of transcription is underexplored. We have designed and synthesized a series of uracil 2ʹ-deoxyribonucleosides and 5ʹ-O-triphosphates (dNTPs) bearing diverse modifications at position 5 of nucleobase, including natural nucleotides occurring in bacteriophages, α-putrescinylthymine, α-glutaminylthymine, 5-dihydroxypentyluracil, and methylated or non-methylated 5-aminomethyluracil, and non-natural 5-sulfanylmethyl- and 5-cyanomethyluracil. The dNTPs bearing basic substituents were moderate to poor substrates for DNA polymerases, but still useful in primer extension synthesis of modified DNA. Together with previously reported epigenetic pyrimidine nucleotides, they were used for the synthesis of diverse DNA templates containing a T7 promoter modified in the sense, antisense or in both strands. A systematic study of the in vitro transcription with T7 RNA polymerase showed a moderate positive effect of most of the uracil modifications in the non-template strand and some either positive or negative influence of modifications in the template strand. The most interesting modification was the non-natural 5-cyanomethyluracil which showed significant positive effect in transcription.